Synthesis of Carbon Nano Fibers: Fabrication and Characterization of Carbon Nano Fibers/rea-formaldehyde Resin - Khan, Tanveer Ahmed; Gupta, Arun; Saidatul Shima, Jamari; Poddar, Pradeep Kumar (Asian Online Journals, 2014)
This paper addresses fabrication of carbon nano fibers by pyrolysis of wood fibers and their dispersion in urea formaldehyde with an aim to optimize a stable carbon nano fibers/urea formaldehyde resin. All the resin hybrids were characterized with Fourier transform infrared spectroscopy (FTIR) and powder X-ray diffractometry (XRD), while the dispersion of carbon nano fibers particles was studied with Field Emission scanning electron microscopy (FESEM). Thermo gravimetric analysis (TGA) revealed that carbon nano fibers have little high effect in the thermal stability of the UF resin. From the TGA graph, it is observed that the thermal stability of the UF based carbon nano fibers is higher than UF only. The scanning micrographs provided evidence of the smoother surfaces in the UF resin made with carbon nano fibers. This was attributed to the better encapsulation of fibers by the matrix polymer.